Assessment of paravalvular regurgitation after transcatheter aortic valve replacement by hemodynamic measurements and cardiac magnetic resonance (APPOSE trial). (3rd October 2022) - Rooijakkers, M J P; Stens, N A; Van Wely, M H; Van Der Wulp, K; Rodwell, L; Gehlmann, H; Van Garsse, L A F M; Geuzebroek, G S C; Verkroost, M W A; Habets, J; El Messaoudi, S; Thijssen, D H J; et al.
Abstract: Background: Paravalvular regurgitation (PVR) is a common complication after transcatheter aortic valve replacement (TAVR) which poses an increased risk of rehospitalization for heart failure and mortality. Purpose: To assess the accuracy of hemodynamic indices to detect relevant PVR as compared to gold-standard cardiac magnetic resonance (CMR) quantitative flow assessment. Methods: In this prospective single-centre clinical trial, four hemodynamic indices of PVR measured directly after TAVR were assessed for their correlation with CMR regurgitant fraction (CMR-RF) at one month follow-up: diastolic delta (DD), heart rate adjusted diastolic delta (HR-DD), aortic regurgitation index (ARI) and aortic regurgitation index ratio (ARI ratio). The hemodynamic indices were analyzed for their ability to detect relevant PVR (defined as more than mild PVR, CMR-RF >20%) using receiver operating characteristic (ROC) curves. Results: We examined 77 patients in whom CMR was performed one month after TAVR. Mean age was 80.4±5.1 years and 46.8% of patients were men. Mean CMR-RF was 12.4±9.3%. Sixty-two (80.5%) patients had ≤ mild PVR (CMR-RF ≤20%), 14 (18.2%) patients had moderate PVR (CMR-RF 21–39%) and one (1.3%) patient had severe PVR (CMR-RF ≥40%). DD was the best hemodynamic index to discriminate between relevant and non-relevant PVR (area under the curve (AUC) 0.82; 95% CI, 0.72–0.92), followed by HR-DD (AUC 0.78; 95% CI 0.67–0.89), ARI (AUC 0.78, 95% CI 0.66–0.89) and ARI ratio (AUC 0.65; 95% CI 0.49–0.81). Conclusions: Diastolic delta measured directly after TAVR has a high accuracy to predict relevant PVR at one month follow-up as assessed by CMR. Correction for heart rate (HR-DD) or systolic blood pressure (ARI, ARI ratio) does not improve this accuracy. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott Medical